ANALISIS PENERAPAN HOSPITALITY, HYGINE DAN SANITASI PADA USAHAKULINER DIKAWASAN WISATA SETU BABAKAN DI JAGAKARSA JAKARTA SELATAN - Wiriadi Sutrisno; Siswi Wulandari; Nur Sodik (UNIVERSITAS INDRAPRASTA PGRI, 2016)
The success key to culinary business is not only depend on quality products, but also on other significat factors such as hospitality, hygiene and sanitation are said as HHS in running the culinary business getting succes. However, those three factors, don’t put on serious attention, especially for the Business Actor Micro (PUM), who worked in the food as well as culinary business, even for the beginers as well as the experieinced one, especially in tourist areas Setu Babakan, South Jakarta. Therefore,suppose HHS practices in operations will not be optimalize, in the long term, these conditions would have a negative impact to culinary business as well as the tourism business overall in Setu Babakan. PUM in Setu Babakan,’s donethe businessjust on conventionally based. They run all processing steps, start from raw materials handler to the serving to the customer, just ignoring the HHS factors. Processed foods that will be served directly to customers, is still done by gloveless. Similarly, where all kitchen workers are not using an apron, which limits to groceries vulnerable infestation microbiology and mor that those, there is no hospitality in serving as well ingreating to the customers. This study aims to find out how to PUM be aware that HHS is very important in business they are doing and how toform suitable training for the PUM (Training Need Assesment/TNA), so they can run the culinary business by applying HHS firmly as well.